STUDI EKOLOGI POHON KEPAYANG (Pangium edule Reinw.) DI AREAL GARAPAN KELOMPOK TANI HUTAN KARYA MAKMUR II DALAM TAHURA WAN ABDUL RACHMAN - Yudha, Aditya Prima (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
Wan Abdul Rachman Grand Forest Park is one of the forest areas that is quite important and certainly beneficial to the community. This utilization can be done by farmers who are members of forest farmer groups (KTH) who have been given utilization permits by the government. One of the KTHs in Wan Abdul Rachman Grand Forest Park is Karya Makmur II KTH, which in its cultivated area has a tree that is already rare, namely the kepayang tree (Pangium edule Reinw.). The objectives of this research are to determine the ecological conditions and the level of association of kepayang trees in the cultivated area of KTH Karya Makmur II. The method used was an exploration method in which the plot was made based on the presence of kepayang trees. The results showed that the kepayang tree population in the cultivated area of the Karya Makmur II Forest Farmers Group was found at an altitude of 155-161 m above sea level, land slope of 25-45%, air temperature 29.2-31.9 Â° C, air humidity 55-71%, soil pH 6.5-7, soil type dystropepts, and rainfall 201 mm/month. The highest level of association occurred between kepayang trees and melinjo trees with an OI of 0.91.